The Population Divide in India: Opportunities and Policies - Vashishat, Aarushi (Journal of Global Economy, Business and Finance, 2026)
This article explores India’s demographic dividend, highlighting the potential for rapid economic growth and social advancement that arises when a nation’s working - age population surpasses its youth and elderly dependents. As of 2021, India was poised to benefit from this demographic advantage with a youthful population, low dependency ratio, and median age of 29 years, making it one of the world’s youngest countries. However, to fully harness this dividend, India must address key objectives, including economic development, employment generation, skill development, quality education, health, gender equality, infrastructure, social security, technological advancement, entrepreneurship, regional development, and sustainable practices. A literature review underscores the significance of these factors in realizing the demographic dividends potential and highlights the need for comprehensive policies and strategic planning. The article emphasizes the urgency of capitalizing on this unique opportunity while preparing for future demographic shifts.